2008
DOI: 10.1002/jip.74
|View full text |Cite
|
Sign up to set email alerts
|

To link or not to link: a test of the case linkage principles using serial car theft data

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
134
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(149 citation statements)
references
References 26 publications
13
134
1
1
Order By: Relevance
“…With this caution in mind, it can be said that the findings lend further support to the notion that offenders tend to commit their offenses in relatively restricted geographical areas and temporal periods that do not overlap significantly with those of other offenders (e.g. Bennell & Canter, 2002;Tonkin et al, 2008;Woodhams & Toye, 2007). But, they extend this conclusion beyond specific crime types, which suggests that the offenders in this sample offend in broadly the same geographical regions, regardless of crime type.…”
Section: Running Head: Linking Different Types Of Crime 23supporting
confidence: 72%
“…With this caution in mind, it can be said that the findings lend further support to the notion that offenders tend to commit their offenses in relatively restricted geographical areas and temporal periods that do not overlap significantly with those of other offenders (e.g. Bennell & Canter, 2002;Tonkin et al, 2008;Woodhams & Toye, 2007). But, they extend this conclusion beyond specific crime types, which suggests that the offenders in this sample offend in broadly the same geographical regions, regardless of crime type.…”
Section: Running Head: Linking Different Types Of Crime 23supporting
confidence: 72%
“…Based on such theories and on research fi ndings from studies of non-criminal behaviour (Pervin, 2002), it was suggested that we might observe greater behavioural similarity in the commission of serial crimes that are temporally more proximate . This hypothesis has now been tested by two studies of serial car theft (Tonkin et al, 2008) and serial sex offences (Woodhams, Hollin, & Bull, 2008) but no such relationship has been found. The current study also sought to extend such research to serial burglary.…”
mentioning
confidence: 85%
“…Studies sampling serial burglaries and serial car theft have indeed reported that geographical proximity (inter-crime distance) and temporal proximity outperform more traditional modus operandi behaviours (e.g. entry method, property stolen) (Bennell & Canter, 2002;Bennell & Jones, 2005;Goodwill & Alison, 2006;Tonkin et al, 2008). Linked crime pairs are consistently found to be closer in time and space than unlinked crime pairs.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…More recently, the notion of offense consistency has been applied to geographic and spatial behaviors, which can be seen as less situation dependent. So far, study findings show that these aspects of a crime could in fact outperformed traditional modus operandi behaviors (e.g., Bernasco, 2008;Goodwill & Alison, 2006;Markson et al, 2010;Tonkin, Grant, & Bond, 2008). For example, Bennell and Jones (2005) argued that the location chosen to commit a crime is a decision that the offender has control over and is less dependent on the situation.…”
mentioning
confidence: 95%